Self-determination, healthcare treatment and minors in Italian clinical practice: ethical, psychological, juridical and medical-legal profiles - Ciliberti, Rosagemma; Alfano, Linda; Baldelli, Ilaria; De Stefano, Francesco; Bonsignore, Alessandro (Acta Biomedica Atenei Parmensis, 2018)
Background and aim: The social role of the minor, as indeed that of the physician, has changed markedly. This transformation has given rise to new patterns and responsibilities in the management of healthcare procedures that involve minors. Discussion: According to international legislation, in the clinical setting, as in other areas of social life, minors have the right to be heard and to have their opinions taken into consideration as an increasingly determining factor, in accordance with their age and degree of maturity and discernment. The authors describe the right to information and the decision-making process when the patient is a minor and underline the role of the parties involved (physicians, parents, under-age patient, judge) in various circumstances. Specifically, the paper analyzes the ethical and legal issues relating to the entitlement to decisions concerning the medical treatment of children and assesses the importance that Italian law attaches to the will of minors in the healthcare choices that affect them. Conclusions: Healthcare workers are called upon to face new challenges in order to ensure that healthcare services are able to safeguard the interests of minors while, at the same time, respecting their will. How to evaluate children’s competence to consent and how to balance the autonomy of parents and minors are crucial questions which the law courts in the various countries are increasingly being asked to address. These issues require close collaboration among various figures (parents, doctors, psychologists, judges) and imply the ethical need to undergo continuous training.